Controllable Solution‐Phase Epitaxial Growth of Q1D Sb2(S, Se)3/CdS Heterojunction Solar Cell with 9.2% Efficiency. Issue 44 (12th September 2021) - Jin, Xin; Fang, Yanan; Salim, Teddy; Feng, Minjun; Yuan, Zhengtian; Hadke, Shreyash; Sum, Tze Chien; Wong, Lydia Helena
Abstract: Antimony sulfoselenide (Sb2 (S, Se)3 ) is a promising photoabsorber for stable and high efficiency thin film photovoltaics (PV). The unique quasi‐1D (Q1D) crystal structure gives Sb2 (S, Se)3 intriguing anisotropic optoelectronic properties, which intrinsically require the optimization of crystal growth orientation, especially for electronic devices with vertical charge transport such as solar cells. Although the efficiency of Sb2 (S, Se)3 solar cells has been improved greatly through optimizing the material quality, the fundamental issue of crystal orientation control in polycrystalline films remains unsolved, resulting in charge carrier recombination losses in the device. Herein, the epitaxial growth of vertically‐oriented Sb2 (S, Se)3 film on hexagonal CdS is successfully realized via a solution‐based synergistic crystal growth process. The crystallographic orientation relationship between Sb2 (S, Se)3 light absorber and the CdS substrate has been rigorously investigated. The best performing Sb2 (S, Se)3 solar cell shows a high power conversion efficiency of 9.2% owing to the faster charge transport in the bulk and the efficient charge extraction across the heterojunction. This study points to a new direction to control the crystal growth of mixed‐anion Sb2 (S, Se)3, which is crucial to achieve high efficiency solar cells based on antimony chalcogenides with low dimensionality. Abstract : A solar cell device based on ( hk 1)‐oriented Sb2 (S, Se)S3 grown on top of hexagonal CdS is successfully prepared. The enhanced device performance is attributed not only to the faster charge transport along the vertically oriented (Sb4 X6 ) n ribbons, but also to the efficient charge extraction across the heterojunction owing to the formation of favorable covalent bond at the junction.